Analisis Kemampuan Berpikir Kreatif dalam Pembelajaran Biologi pada Siswa Kelas XI SMA Negeri 1 Kampung Rakyat - Yuliarni, Yuliarni; Machrizal, Rusdi; Harahap, Hasmi Syahputra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
When it comes to the cultivation of human resources for the purpose of achieving a more favorable future, education is basically an imperative prerequisite. The ability to think creatively plays a significant part in higher order thinking since creativity is the factor that influences the amount and kind of qualitative research that is conducted using descriptive techniques. The population that was utilized consisted of students who were enrolled in the first semester of biology instruction at SMA N 1 Kampung Rakyat. A total of 36 individuals were selected for sampling. Interviews are employed as a method of data gathering, and the strategy that is used in data collecting is the distribution of a questionnaire. The findings of the investigation into the analysis in this particular instance indicate that the investigation into the creative thinking abilities of students in class XI at SMA Negeri 1 Kampung Rakyat was conducted in order to learn about biology. That in the first indicator Fluency obtained results totalling 58.33% while in the second indicator Flexibility obtained results totalling 57.87% and in the third indicator Originality obtained results totalling 59.56%. As well as in the fourth indicator Thinking Fluently (Fluency) obtained results totalling 59.56%. As well as in the fourth indicator of Detailed Thinking (Elaboration) obtained a value of 64.89%. In this case, creative thinking in the world of education is a very important thing in obtaining good learning.